2016
DOI: 10.1007/s11104-016-2999-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant functional type on methane dynamics in a restored minerotrophic peatland

Abstract: Background and Aims: Peatland methane (CH4) fluxes may vary between plant types; however, in mixed communities, the specific role of each species is difficult to distinguish. The goal of this study was to determine the individual and interacting effect of moss, graminoid and shrub plant functional types on CH4 dynamics of experimentally planted plots in a rewetted minerotrophic peatland Methods: We measured CH4 flux, pore water CH4 concentration and CH4 production and oxidation potential in pure stands of rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 73 publications
0
33
0
Order By: Relevance
“…Wildfires can reduce methanotroph activity in peat (Danilova et al, 2015) but the low fire-induced belowground heating at the raised bog (maximum soil temperature was 15 • C; Table 1) suggests that aboveground changes in vegetation were likely key in explaining differences in CH 4 flux between unburnt and burnt plots (Levy et al, 2012;Gray et al, 2013). For example, bryophytes can host symbiotic methanotrophic bacteria (Strack et al, 2017) and vascular plants have been linked to methanotroph abundance (Chen et al, 2008) and can promote methanotroph activity through diffusion of oxygen to the root zone (Ström et al, 2005). Vegetation can also influence CH 4 flux by facilitating its transport from anaerobic peat layers to the atmosphere, therefore bypassing methanotrophs.…”
Section: Methanementioning
confidence: 99%
See 1 more Smart Citation
“…Wildfires can reduce methanotroph activity in peat (Danilova et al, 2015) but the low fire-induced belowground heating at the raised bog (maximum soil temperature was 15 • C; Table 1) suggests that aboveground changes in vegetation were likely key in explaining differences in CH 4 flux between unburnt and burnt plots (Levy et al, 2012;Gray et al, 2013). For example, bryophytes can host symbiotic methanotrophic bacteria (Strack et al, 2017) and vascular plants have been linked to methanotroph abundance (Chen et al, 2008) and can promote methanotroph activity through diffusion of oxygen to the root zone (Ström et al, 2005). Vegetation can also influence CH 4 flux by facilitating its transport from anaerobic peat layers to the atmosphere, therefore bypassing methanotrophs.…”
Section: Methanementioning
confidence: 99%
“…However, burning is also associated with warmer soils (Grau-Andrés et al, 2018a) that can lead to increased ER (Walker et al, 2018) and methane (CH 4 ) flux (Turetsky et al, 2014). In the longer term, post-fire changes in vegetation community composition (Grau-Andrés et al, 2019) may have the largest impact on soil C dynamics due to differences in C cycling between plant functional groups (Ward et al, 2009;Strack et al, 2017), including litter quality (Wardle et al, 2012) and transport mechanisms (e.g. aerenchymatous species can facilitate methane emission; Gray et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, there can also be a lag effect occurring during water-table fluctuations, with higher CH 4 emissions being recorded on water table drawdowns and drought periods and lower fluxes as the water table increases again (Brown et al, 2014). It is incredibly important that interannual variability is taken into account when measuring carbon fluxes, given the large range in annual flux that can occur (e.g., Roulet et al, 2007) in response to variable conditions arising from many sources including localised microtopography (Crestio Aleina, Runkle, Brücher, Kleinen, & Brovkin, 2016), temperature and hydrological regimes (Bubier, Moore, Savage, & Crill, 2005;Waddington et al, 2015), and vegetation cover (Strack et al, 2017;Ström, Mastenapov, & Christensen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, Godin et al (2012) found greater diversity in the methanogenic community and active rates of methanogenesis in rich fens across a gradient of fen types, but soil wetness was not a good predictor. Several studies have singled out graminoids in peatlands for their role in methanogenesis (cf., Treat et al, 2015;Strack et al, 2017), given that they assume dominance in rich fens (Schwintzer, 1981).…”
Section: Methanogenesis and Anaerobic Respirationmentioning
confidence: 99%